Teacher and child : - Ginott, Haim G. (Macmillan, 1972)
The author suggests concepts, attitudes and a language of acceptance and compassion to improve daily situations and psychological problems faced by teachers. He applies his ideas to problems of discipline, criticism, anger, motivation, homework, praise, cooperation, and the conflicting relationships of students, teachers, administrators and parents.